The higher level of organization of the oxidative phosphorylation system: mitochondrial supercomplexes - Dudkina, Natalya V. (Springer US, 2008)
The organization of the oxidative phosphorylation (OXPHOS) system within the inner mitochondrial membrane appears to be far more complicated than previously thought. In particular, the individual protein complexes of the OXPHOS system (complexes I to V) were found to specifically interact forming defined supramolecular structures. Blue-native polyacrylamide gel electrophoresis and single particle electron microscopy proved to be especially valuable in studying the so-called “respiratory supercomplexes”? Based on these procedures, increasing evidence was presented supporting a “solid state” organization of the OXPHOS system. Here, we summarize results on the formation, organisation and function of the various types of mitochondrial OXPHOS supercomplexes.